The study on relationship of Corporate Social Responsibility (CSR) and employee’s commitment with organizational performances / Nur Fasihah Che Md Azim and Noramirah Bidin - Che Md Azim, Nur Fasihah; Bidin, Noramirah (2013)
There are many factors that can contribute to the increase in organizational performances. The performances of the organization used to be measure by looking at the financial competitiveness of the company and the company only care on how to gaining as mush profit they can. Nowadays, the organization comes with a broader concept to gain success by focuses on maintaining the growth of organization. Many companies nowadays practice the Corporate Social Responsibility (CSR) and having employee’s organizational performances to improve the organizational performances other than having product development and strong financial strength. That is why the purpose of this study aimed to study the significant relationship between the practices of the CSR by the company and having employee’s commitment will it boost the organizational performances other usual factor. The analytical model has developed to study the relationships between organizational performances (dependent variables) with CSR and employees’ commitment (independent variables). A quantitative method is chosen in this research. The researcher distributes the questionnaire to gather the primary sources data. 100 questionnaires being distribute and 88 questionnaires is return back. The SPSS is use to analysis and process the data collect. The findings show that the practices of the CSR and having the employee’s organizational commitment are positively related and able to influence the organizational performances.